Tracking System for Wireless Devices in Wifi Environment (International Journal of Engineering and Computer Science, 2017)
Growing convergence among mobile computing devices and embedded technology sparks the development and deployment of “context-aware” applications, where location is the most essential context. In this paper, we introduce a similar forensic surveillance tool for wireless networks. Our system, for wireless network can reveal the locations of WiFi-enabled mobile devices within the coverage area of a high-gain antenna. it features a mobile design that can be quickly deployed to a new location for instant usage without training. We present a comprehensive set of theoretical analysis and experimental results which demonstrate the coverage and localization accuracy of the design framework.